HUBUNGAN PENGETAHUAN MENYIKAT GIGI TERHADAP SIKAP MENYIKAT GIGI MENYIKAT GIGI MURID SDN KELAS VI DI KELURAHAN PUHUN PINTU KABUN KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Aflinda Yenti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Tooth brushing is one of the simplest ways to clean the tooth surface from food debris that sticks to the teeth which can cause caries and tissue damage to the periodontium, to be able to do this certainly begins by having good knowledge about brushing teeth followed by a good attitude about brushing teeth. This study aims to determine the relationship between knowledge of brushing teeth and brushing teeth in elementary school students. The study design was an analytical survey with a cross sectional approach. The population of this study was all students of Class VI SDN in Puhun Pintu Village, Kabun, Mandiangin Subdistrict, Koto Selayan, Bukittinggi City, amounting to 63 students. Data is collected using a questionnaire and processed using a computer program. This study concludes that there is a relationship between the knowledge of brushing teeth with the attitude of brushing teeth for students of Class VI SDN in Puhun Pintu Kabun Village, therefore it is expected that students will improve their knowledge about brushing so that their attitude towards brushing teeth will be better. Keywords